2005
DOI: 10.1093/bioinformatics/bti1113
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in Ciona intestinalis

Abstract: www.bioinf.uni-leipzig.de/Publications/SUPPLEMENTS/05-008/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 9 publications
2
42
0
Order By: Relevance
“…An RNAz survey based on the most conserved parts of the vertebrate genomes estimates that the ncRNA content of mammalian genomes is comparable to their protein coding genes (Washietl et al, 2005b), and hence at least an order magnitude larger than in nematodes. In contrast, the predicted number of structured RNAs in the urochordate Ciona intestinalis is comparable to our results for the nematodes (Missal et al, 2005). This indicates that higher vertebrates have dramatically expanded their ncRNA inventory relative to their complement of protein coding genes.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…An RNAz survey based on the most conserved parts of the vertebrate genomes estimates that the ncRNA content of mammalian genomes is comparable to their protein coding genes (Washietl et al, 2005b), and hence at least an order magnitude larger than in nematodes. In contrast, the predicted number of structured RNAs in the urochordate Ciona intestinalis is comparable to our results for the nematodes (Missal et al, 2005). This indicates that higher vertebrates have dramatically expanded their ncRNA inventory relative to their complement of protein coding genes.…”
Section: Discussionsupporting
confidence: 76%
“…A similar analysis of the genomes of urochordates (Missal et al, 2005), on the other hand, identified only a few thousand putative structured RNAs, consistent with the hypothesis that ncRNAs form the basis of a complex cellular regulation system that has been vastly expanded in vertebrates (Mattick, 2004;Bartel and Chen, 2004). Here we extend the phylogenetic range of systematic surveys for ncRNAs to nematodes.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, we come close the results of a comparative genomics screen for non-coding RNAs in C. elegans [49], which reported 12 U1, 19 U2, 5 U4, 13 U5, and 23 U6, i.e., only a few more candidates than our present purely homology-based approach. A comparative screen of the two Ciona species for evolutionary conserved structured RNAs [48] missed a small number of snRNA genes that we indentified as most likely functional ones.…”
Section: Homology Searchmentioning
confidence: 93%
“…Although a number of studies have successfully identified ncRNAs in several animal (Missal et al 2005;Washietl et al 2007) and microbial genomes (Altuvia 2007), the pace at which such studies are performed and published lags far behind the rate of genome sequence output. Most of the complete genomes sequenced to date have escaped the scrutiny of RNA experts, and their potential for novel RNA functions lies unexplored.…”
mentioning
confidence: 99%